Arrived in Power, and Yet Still Disgruntled? How Government Inclusion Moderates 'Protest Voting' for Far-Right Populist Parties in Europe. Issue 4 (12th October 2022) - Muis, Jasper; Brils, Tobias; Gaidytė, Teodora
Abstract: While debates about far-right populism often concentrate on Central and Eastern Europe, research on these parties predominantly focuses on Western countries. Addressing this remarkable gap, this article revisits the 'protest voting' explanation for electoral support for the far right. Using European Social Survey data (2002–16) from 22 countries, we show that political dissatisfaction is a stronger explanatory factor when far-right parties are in opposition, but is a less important determinant of electoral support when they are in government. Previous findings based on Western Europe – which similarly showed that the anti-elite hypothesis is less relevant when far-right parties join government coalitions – travel well to post-communist European countries. In Hungary and Poland, we even find that far-right voters have become less distrustful of national political institutions than the rest of the electorate. Our conclusion implies that anti-elite populism is context-dependent and has limited use for understanding successes of leaders such as Wilders, Salvini and Orbán.